Caracterização molecular de acessos de jabuticabeiras do banco ativo de germoplasma da UTFPR com marcadores microssatélites - Martins, Diego Albino (2013)
Brazil is a country of great biodiversity holder, however small portion of that has been studied and cataloged. Recent advances human activities on natural ecosystems has led to its rapid fragmentation and elimination of some biotypes still, not it studied or cataloged. In this reality of genetic erosion is also accelerated jabuticaba tree species (Plinia sp.). That are endemic from South Central / Southeastern Paraná State, in Araucaria forest ecosystem. Germplasm conservation measures for current and future use, as well as tactics for management and conservation of natural resources are crucial to minimize the damage caused to Brazilian biodiversity. So it is necessary to understand the genetic diversity in natural ecosystems, which is the basic input for the survival and evolution among individuals facing environmental changes. In the present study was to characterize genetic of 110 jabuticaba tree fruit, that constitute the germoplasm bank of jabuticaba tree fruit from UTFPR - Câmpus Dois Vizinhos. It was possible to identify transferability of 9 microsatellite markers (SSR) with polymorphic character for the population studied, and it carry out standardization of PCR reaction for each of them. The analysis of plant germoplasm bank came to the conclusion that houses a considerable amount of allelic diversity, but this diversity is poorly distributed, since 11 individuals alone are already able to represent 59.2% of all alleles of the collection of 110 plant. The found values of, observed heterozygosity and information content (PIC) in this subpopulation of 11 individuals were higher than the values found for the full set of the germoplasm bank. The grouping of individuals showed the existence of 8 different groups, and 89 subjects were in group 1, demonstrating a possible relationship and low level of genetic diversity.